Metabolic Properties of Early and Late Vaccinia Virus Messenger Ribonucleic Acid - Sebring, E. D. (1967)
In vaccinia-infected cells, 60% of the viral messenger ribonucleic acid (mRNA) was associated with polyribosomes, and the remainder sedimented in a broad peak in the 30 to 74S region. The quantity of mRNA in polyribosomes was sharply reduced late in the infectious cycle [9 hr postinfection (PI)] to less than 30% of the 2-hr value. However, protein synthesis proceeded at a nearly constant rate from 2 to 13 hr PI. This ability of small quantities of late mRNA to support as much protein synthesis as do the much larger quantities of early mRNA was not due to an increase in stability, since late mRNA decays with a half-life of 13 min, whereas early mRNA has a half-life of 120 min. A similar decrease in viral mRNA synthesis without an accompanying decrease in viral protein synthesis was observed when deoxyribonucleic acid synthesis is inhibited. In contrast to the rapid decay of the late mRNA which was present in polyribosomes, the mRNA which sedimented in the 30 to 74S region remained unchanged even after a 2-hr period of exposure to actinomycin. The rate at which infected cells lose the capacity to synthesize specific viral proteins after exposure to actinomycin D was consistent with the half-life values of early and late mRNA that were observed.